Educação para o Antropoceno: sustentabilidade ambiental na Rede Federal de Ensino Profissional Científico e Tecnológico - Maruyama, Úrsula Gomes Rosa (2019)
The change in the use of natural resources on our planet is a most urgent topic to be addressed in the environmental agendas of all governments and discussed by civil society and the academic community. As a consequence of this period known as Anthropocene, global warming is one of the most critical issues on the environmental agenda in the 21st century as it affects biogeochemical cycles and planetary biodiversity. Considering the need to provide institutional spaces of dialogue and legitimation for a whole of society, public education is a prime factor in the dissemination of scientific information to society and the promotion of debates on ecological crisis. Through the concept of information system, a critical analysis of the relations between actors, mediation processes and informational practices was developed in the Federal Network of Professional Scientific and Technological Teaching (RFEPCT). For that, a field and documentary research was carried out, where the concept of information regime was applied in order to characterize and evaluate how the ITS of the RFEPCT are acting as disseminators of an education focused on the challenges of the Anthropocene.